2021
DOI: 10.3390/jcm10030494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corticosteroid Administration within 7 Days of the Hospitalization for Influenza Pneumonia with Respiratory Failure: A Propensity Score Analysis Using a Nationwide Administrative Database

Abstract: Influenza pneumonia, which causes acute respiratory distress syndrome and multiple organ failure, has no established management protocol. Recently, corticosteroid therapy was used to treat coronavirus disease 2019 with respiratory failure; however, its effectiveness as a treatment for influenza pneumonia remains controversial. To investigate the impact of corticosteroid therapy for the early phase of severe influenza pneumonia, we compared influenza pneumonia patients with respiratory failure treated with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…[13][14][15][16][17][18] The remaining 14 studies included only sepsis with pneumonia, perforation of the lower gastrointestinal tract, or shock. 12,[19][20][21][22][23][24][25][26][27][28][29][30][31] Four studies on patients with sepsis overall were based on the same cohort [13][14][15][16] (Table 1).…”
Section: R E Su Ltsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18] The remaining 14 studies included only sepsis with pneumonia, perforation of the lower gastrointestinal tract, or shock. 12,[19][20][21][22][23][24][25][26][27][28][29][30][31] Four studies on patients with sepsis overall were based on the same cohort [13][14][15][16] (Table 1).…”
Section: R E Su Ltsmentioning
confidence: 99%
“…The claims-based database has population-based statistics on diagnosis, treatment, and medical costs during hospital stays, covering more than 80% of all acute care hospitals in 2019. 12 Using this database, several epidemiological studies have revealed an increasing number of patients with sepsis and an escalating cost of sepsis-related medical care in Japan's super-aging society 13,14 ; however, there is a lack of literature review to obtain a comprehensive understanding of population-based studies in Japan. In this review, we describe the epidemiology, clinical management, and medical costs of patients with sepsis who had an infection and organ dysfunction, which is linked with Sepsis-3 using a Japanese administrative database.…”
mentioning
confidence: 99%
“…A retrospective observational study published in 2021 that used propensity score analysis reported that 25% of the study population received systemic corticosteroids within 7 days of hospital admission. The author found an increased risk of mortality in patients with severe influenza pneumonia, even if corticosteroids were started within this period [ 141 ]. The current recommendations from the American Thoracic Society and Infectious Diseases Society of America are against the use of corticosteroids in adults with severe influenza pneumonia (this is a conditional recommendation with low-quality evidence) [ 122 ].…”
Section: Corticosteroids: Benefit or Harmmentioning
confidence: 99%
“…68 A retrospective observational study using propensity score analysis suggested that there may be increased risk of mortality even if the corticosteroids are used within 7 days of hospitalization for influenza. 69 Another observational study of 2141 hospitalized patients with influenza showed that low-to-moderate-dose (25–150 mg/day methylprednisolone equivalent) was actually associated with lower mortality compared to no treatment (HR 0.64; 95% CI, 0.43–0.96). 70 However, high-dose corticosteroid therapy resulted in no difference in mortality but in the subgroup of patients with mild disease (PaO 2 /FiO 2 ≥ 300 mmHg) 60-day mortality was increased (HR 3.02; 95% CI, 1.06–8.58).…”
Section: Potential Harms Of Corticosteroidsmentioning
confidence: 99%